TRAINING OF THE NATIONAL SECURITY MASTERS: ENGLISH FOR SPECIFIC PURPOSES - Наталія КАЛИНЮК; Ольга ЛЕМЕШКО (Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine, 2022)
The article deals with the peculiarities of educational program of the second (master's) level of higher education in specialty 256 "National security (by certain activities and areas of security)" and working curriculum "English for Specific Purposes". The structure of educational program and working curriculum was investigated. The purpose of the educational program is to ensure the training of highly qualified masters of national security of strategic level of higher military education, able to effectively manage the activities of the central executive body and its territorial bodies, to implement state policy in border activities (security of Ukraine's state border and protection of Ukraine's sovereign rights) in its exclusive (maritime) economic zone). Issues of the further training, teaching and training, assessment, program competences (integral competence, general competencies and professional competencies), program learning outcomes, the list of the education program components (mandatory and selective) were studied. We investigated the working curriculum "English for Specific Purposes" that lasts 2 years based on the first (Bachelor's) level of higher education. The main task of the academic discipline is to prepare students for foreign language communication in English in the field of cross-border activities. Within the scope of the course, specialist training is carried out by imparting knowledge, developing skills and forming practical skills necessary for the performance of duties in operational-strategic level positions. Upon the completion of educational program officers take complex operational-strategic task and exam. The complex operational-strategic task is aimed at learning of the main terms used in the design of graphic documents in the armies of the NATO countries. The task of exam is to determine the level of mastering the students of foreign language communicative competence, as well as skills of translating texts on professional topics; to determine the level of knowledge of lexical material, the formation of skills and development of students' skills in the scope of the curriculum; to obtain information to optimize the educational work of the students and to improve the methodology of training. The discipline knowledge is examined in the form of a test task and a written translation of the text of professional orientation.